2012
DOI: 10.1007/s10562-012-0770-z
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Schiff Base Complex Covalently Anchored to Silica-Coated Cobalt Ferrite Nanoparticles as a Novel Heterogeneous Catalyst for the Oxidation of Alkenes

Abstract: Silica-coated cobalt ferrite nanoparticles were prepared and functionalized with Schiff base groups to yield immobilized bidentate ligands. The functionalized magnetic nanoparticles were then treated with Mo (O 2 ) 2 (acac) 2 , resulting in the novel immobilized molybdenum Schiff base catalyst. The as-prepared catalyst was characterized by X-ray powder diffraction, transmission electron microscopy, vibrating sample magnetometry, thermogravimetric analysis, Fourier transform infrared, and inductively coupled pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…[41] (m) Mo-salenSi@Si-MNPs. [42] [43] (MoO 2 salpr@MCM-41), [44] MoO 2 Sal@MCM-41, [45] results showed that MoO 2 Sal/APTSCMNPs are more active in cyclohexene epoxidation in the same reaction conditions due to the fact that MoO 2 Sal/APTSCMNPs has better site isolation, insignificant pore diffusion limitations and relatively strong interaction between the chelating ligand and the Mo center.…”
Section: Magnetic Particles Supported Mo-based Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…[41] (m) Mo-salenSi@Si-MNPs. [42] [43] (MoO 2 salpr@MCM-41), [44] MoO 2 Sal@MCM-41, [45] results showed that MoO 2 Sal/APTSCMNPs are more active in cyclohexene epoxidation in the same reaction conditions due to the fact that MoO 2 Sal/APTSCMNPs has better site isolation, insignificant pore diffusion limitations and relatively strong interaction between the chelating ligand and the Mo center.…”
Section: Magnetic Particles Supported Mo-based Catalystsmentioning
confidence: 99%
“…(l) MoO 3 (sal‐phz)Fe 3 O 4 ‐SBA‐15(3B) . (m) Mo‐salenSi@Si‐MNPs . (n) (MoO(O 2 ) 2 (phox)/Fe 3 O 4 ‐SBA .…”
Section: Mo‐based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…[48][49][50][51] Regarding the application of magnetically separable catalysts, there are several reports that investigate the catalytic role of immobilized Mo complex on magnetic nanoparticles in the oxidation of alkenes. [52][53][54][55][56] According to this background, in this study, we report the synthesis and characterization of a new dioxomolybdenum complex with tridentate hydrazone Schiff base ligand ((2-hydroxy-5-nitrobenzylidene) benzhydrazide), followed by immobilization on the modified Fe 3 O 4 nanoparticles. The catalytic activities of both homogeneous and heterogeneous catalysts in the oxidation of various alkenes are evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main drawback of these homogeneous catalysts is the necessity of their separation from the reaction mixture at the end of the reaction. Immobilization of Schiff base complexes to the magnetic nanoparticle support via covalent attachment provides facile separation of the catalyst during the reaction by external magnet [3]. The magnetic support offers high catalytic efficiency and better recycling without having the inherent problems of leaching of complex/ligand during the reaction.…”
Section: Introductionmentioning
confidence: 99%